Common genetic variants associated with pancreatic adenocarcinoma may also modify risk of pancreatic neuroendocrine neoplasms. (22nd December 2017) - Obazee, Ofure; Capurso, Gabriele; Tavano, Francesca; Archibugi, Livia; De Bonis, Antonio; Greenhalf, William; Key, Tim; Pasquali, Claudio; Milanetto, Anna Caterina; Hackert, Thilo; Fogar, Paola; Liço, Valbona; et al.
Abstract : This study identifies an overlap of susceptibility loci between PDAC and pNEN which may provide insights on potentially useful markers for risk stratification and tumor characterization among healthy individuals and pNEN patients, respectively. Abstract: Pancreatic neuroendocrine neoplasms (pNEN) account for less than 5% of all pancreatic neoplasms and genetic association studies on susceptibility to the disease are limited. We sought to identify possible overlap of genetic susceptibility loci between pancreatic ductal adenocarcinoma (PDAC) and pNEN; therefore, PDAC susceptibility variants ( n = 23) from Caucasian genome-wide association studies (GWAS) were genotyped in 369 pNEN cases and 3277 controls from the PANcreatic Disease ReseArch (PANDoRA) consortium to evaluate the odds associated with pNEN risk, disease onset and tumor characteristics. Main effect analyses showed four PDAC susceptibility variants—rs9854771, rs1561927, rs9543325 and rs10919791 to be associated with pNEN risk. Subsequently, only associations with rs9543325, rs10919791 and rs1561927 were noteworthy with false positive report probability (FPRP) tests. Stratified analyses considering age at onset (50-year threshold), showed rs2736098, rs16986825 and rs9854771 to be associated with risk of developing pNEN at a younger age. Stratified analyses also showed some single nucleotide polymorphisms to be associated with different degrees of tumor grade, metastatic potential and functionality. Our results identify known GWAS PDAC susceptibility loci, which may also be involved in sporadic pNEN etiology and suggest that some genetic mechanisms governing pathogenesis of these two entities may be similar, with few of these loci being more influential in younger cases or tumor subtypes.